O strukturze świata w narracyjnych grach wideo - Maj, Krzysztof M. (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The article On the structure of gameworld in narrative video games proposes to introduce the term ‘ludotopia’ to Polish game studies in order to further compartmentalise the structure of video gameworld. Having reflected on the consequences of so-called world-centered turn in contemporary digital humanities, the author proceeds to defining archetypal structures that compose realities designed for the purposes of narrative video games, namely: locations and clusters of locations, the latter divided further into biomes and anthromes. The hierarchy introduced thereby is presented as an alternative for already influential (though, arguably, in transmedial world-building studies rather than game studies) trichotomy of mythos, topos, and ethos, as defined by Lisbeth Klastrup and Susana Tosca. In the end, the article cross-references the new structural hierarchy of ludotopographical components with a matrix of popular fantastic settings, seeking to delineate possible similarities between ludotopias and allotopias that would inform both game scholars and game designers on the ways of rapid prototyping of aesthetically diverse imaginary worlds.